Technological Innovations During the Gupta Period: Development and Impact - Dr Jayant Kumar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The Gupta period saw significant technological and cultural advancements across mathematics, medicine, metallurgy, and textiles. Innovations such as the concept of zero and the decimal system, credited to Āryabhaṭa and Brahmagupta, revolutionized mathematics and laid the groundwork for modern computing. Medical texts like the Suśrutasaṁhitā and Caraka-Saṃhitā introduced advanced surgical techniques and holistic health principles that remain integral to contemporary wellness practices. Metallurgical advancements, exemplified by the corrosion-resistant Iron Pillar of Delhi, continue to inspire modern materials science. The flourishing textile industry, characterized by innovations in weaving and dyeing, contributed significantly to the Gupta Empire's economic prosperity and established its role in global trade networks. Educational and cultural advancements, epitomized by institutions like Nālandā University, promoted interdisciplinary learning and intellectual exchange. Overall, the Gupta period's technological innovations have left a lasting impact on modern society, underscoring the enduring relevance of these ancient contributions to human progress. While the cultural and intellectual achievements of the Gupta period are well-documented, specific technological innovations, their development, and their impact on society have not been extensively explored. This paper will provide a comprehensive understanding of the Gupta period's contributions to human knowledge and progress and underscore the enduring relevance of these ancient innovations in shaping modern society.